Variable thrust and high efficiency propulsion with oscillating foils at high Reynolds numbers. (15th October 2020) - Dave, Mukul; Spaulding, Arianne; Franck, Jennifer A.
Abstract: Bio-inspired oscillatory foil propulsion has the ability to traverse various propulsive modes by dynamically changing the foil's heave and pitch kinematics. This research characterizes the propulsion properties and wake dynamics of a symmetric oscillating foil, specifically targeting the high Reynolds number operation of small to medium surface vessels whose propulsive specifications have a broad range of loads and speeds. An unsteady Reynolds-averaged Navier–Stokes (URANS) solver with a k- ω SST turbulence model is used to sweep through pitch amplitude and frequency at two heave amplitudes of h 0 ∕ c = 1 and h 0 ∕ c = 2 at R e = 1 0 6 . At h 0 ∕ c = 2, the maximum thrust coefficient is C T = 8 . 2 due to the large intercepted flow area of the foil, whereas at a decreased Strouhal number the thrust coefficient decreases and the maximum propulsive efficiency reaches 75%. Results illustrate the kinematics required to transition between the high-efficiency and high-thrust regimes at high Reynolds number and the resulting changes to the vortex wake structure. The unsteady vortex dynamics throughout the heave–pitch cycle strongly influence the characterization of thrust and propulsive efficiency, and are classified into flow regimes based on performance and vortex structure. Highlights: Simulations of oscillating foil propulsion with high heave amplitude at Re = 1 0 6 . Thrust coefficient up to 8.2 and maximum efficiency of 75%. Transition between high-efficiency and high-thrust with minor changes in kinematics. Efficiency at turbulent Reynolds numbers is higher than for low Reynolds number. Propulsive regimes are classified by vortex structure in the wake.